CU06-1004 inhibits the progression of chronic colitis and colitis-associated colorectal cancer by suppressing inflammation - Kim, Dongyeop; Kim, Yeomyeong; Zhang, Haiying; Kim, Ye-Seul; Noh, Minyoung; Bae, Cho-Rong; Kwon, Young-Guen; Ha, Sang-Jun (Frontiers in Pharmacology, 2025)
BackgroundUlcerative colitis (UC), a type of inflammatory bowel disease (IBD), is a chronic inflammatory disorder of the colon. Chronic intestinal inflammation plays a critical role in the increased risk of developing colitis-associated cancer (CAC). CU06-1004, an endothelial dysfunction blocker, can alleviate acute colitis by suppressing inflammation and regulating colonic vascular dysfunction. However, whether CU06-1004 suppresses chronic intestinal inflammation and prevents the development of CAC remains unclear.MethodsIn this study, we investigated the protective effects of CU06-1004 by suppressing inflammation in both the dextran sulfate sodium (DSS)-induced chronic colitis model and the azoxymethane (AOM)/DSS-induced colorectal cancer mouse models. We evaluated the expression of key pro-inflammatory cytokines, assessed histological characteristics in the animals, and examined the expression of key genes associated with inflammation.ResultsIn the DSS-induced chronic colitis model, our results showed that CU06-1004 treatment suppressed inflammation, as evidenced by disease activity index scores, colon length, colon damage, and histological analysis. Furthermore, CU06-1004 administration reduced the levels of various inflammatory cytokines and factors (tumor necrosis factor-α, interleukin (IL)-1β, IL-6, cyclooxygenase-2, and inducible nitric oxide synthase), decreased immune cell infiltration (F4/80+ macrophages and CD177+ neutrophils), and alleviated inflammation by inhibiting vascular adhesion molecules. Moreover, in the AOM/DSS-induced colorectal cancer model as well, CU06-1004 significantly reduced the severity of colitis. CU06-1004 treatment also significantly reduced both the number and size of AOM/DSS-induced colorectal tumors, suppressed inflammation, and inhibited the malignant proliferation of epithelial cells. Additionally, CU06-1004 treatment downregulated the expression of the key colorectal cancer marker β-catenin and its target gene c-Myc in AOM/DSS-induced mice, thereby inhibiting tumor growth.ConclusionOur findings suggest that CU06-1004 inhibits inflammation-induced tumorigenesis by modulating the inflammatory response in the colon. Consequently, CU06-1004 could represent a promising therapeutic candidate for the prevention of colorectal cancer through modulation of inflammation.